Exposure to second-hand smoke is an independent risk factor of small airway dysfunction in non-smokers with chronic cough: A retrospective case-control study - Zhao, Bingrong; Bai, Lu; Wan, Rongjun; Wang, Yanan; Qin, Ling; Xiao, Qiming; Pan, Pinhua; Hu, Chengping; Jiang, Juan (Frontiers in Public Health, 2022)
Objectives: This study aimed to identify the potential risk factors of SAD in non-smokers with chronic cough. Methods: Non-smokers with chronic cough who took lung function tests at Xiangya Hospital from May 2019 to May 2020 were enrolled, and divided into the derivation and validation cohorts based on their hospital admission time. SAD was determined on the basis of at least two of the following three indicators of lung function being less than 65% of predicted: maximal mid-expiratory flow, forced expiratory flow at 50% of forced vital capacity, and forced expiratory flow at 75% of forced vital capacity. Clinical data of these patients were collected. Logistic regression analysis was used to identify risk factors of SAD in the derivation cohort. Next, risk factors were further confirmed in the validation cohort. Results: A total of 316 patients were included in the derivation cohort, consisting of 152 in SAD group and 164 in non-SAD group. Compared with non-SAD group, SAD group had a higher proportion of females (82.3% vs 59.2%, P < 0.001), were more commonly exposed to second-hand smoke (SHS) (61.6% vs 27.6%, P < 0.001), and tended to be older (median age, 45.5 vs 40.0 years old, P = 0.004). The median forced vital capacity (FVC), forced expiratory volume in one second (FEV1) % pred, FEV1/FVC ratio, and peak expiratory flow (PEF) % pred were slightly lower in SAD group. Multivariable logistic analysis confirmed that exposure to SHS was an independent risk factor (OR 4.166 [95% CI 2.090–8.302], P < 0.001) for SAD in non-smokers with chronic cough after adjusting for related variables. In the validation cohort (n=146), the risk ratio of exposure to SHS was 1.976 (95% CI 1.246-3.135, P = 0.004) for the outcome of SAD. Multivariable logistic analysis consistently showed that exposure to SHS was an independent risk factor (OR 3.041 [95% CI 1.458-6.344], P = 0.003) for SAD in non-smokers. Conclusions: Exposure to SHS is independently associated with higher risk of SAD in non-smokers with chronic cough. Reduction of SHS exposure may ameliorate the lung function, thus lowering the risk of developing irreversible airway obstruction.